Mesalazine-induced lung injury with severe respiratory failure successfully treated with steroids and non-invasive positive pressure ventilation. (2020) - Oi, Hajime; Suzuki, Atsushi; Yamano, Yasuhiko; Yokoyama, Toshiki; Matsuda, Toshiaki; Kataoka, Kensuke; Suzuki, Yasuhiko; Kimura, Tomoki; Kondoh, Yasuhiro
Abstract: Drug-induced lung injury (DLI) has become more common because of the increasing number of therapeutic agents in use. Mesalazine, also known as 5-aminosalicylic acid (5-ASA), is one of the key drugs for the treatment of ulcerative colitis (UC). Although mesalazine-induced lung injury has been previously reported, few cases have included severe respiratory failure. In this report, we present a case of mesalazine-induced lung injury with severe respiratory failure, which was improved by discontinuation of mesalazine and introduction of corticosteroid therapy and ventilation support with non-invasive positive pressure ventilation (NPPV). We also review the previous literature on mesalazine-induced lung injury.